Penerapan Screen Mirroring Android Pada Projector Menggunakan Raspberry Pi - Dwijaya Kongky Salim; Justinus Andjarwirawan; Lily Puspa Dewi (Jurnal Infra, 2019)
In the past, how to use a projector can only be done using a VGA cable which is then connected to a laptop or desktop pc that has a VGA connector, when the projector and laptop or desktop pc are connected, the projector will duplicate the desktop screen of the PC or laptop which will then be displayed on the screen projector In this thesis an application is made to utilize the Gstreamer framework to create applications that can perform screen mirroring and use the Raspberry Pi to display the results of mirroring on the projector, so that users can make presentations using a smartphone and do not need a cable. The application testing results show that delay in mirroring causes the smartphone screen mirrored and displayed on the Raspberry Pi to experience a very slow frame update, due to the Raspberry Pi hardware that doesn't support the Raspberry Pi to mirror smoothly.